Germany : Technical Note on Crisis Management Arrangements. (IMF Staff Country Reports; Country Report, 2011)
This paper discusses Germany's challenges and measures to strengthen crisis management arrangements. Bundesanstalt fur Finanzdienstleistungsaufsicht (BaFin) and the Bundesbank have closely coordinated with the interagency risk committee on banking matters, which also encompasses BaFin representatives for all three financial sectors. The Bundesbank maintains an internal crisis committee and a steering committee. The crisis committee is chaired by a board member and combines expertise from various departments such as banking, financial stability, markets, and payment issues. The German authorities have moved to a comprehensive approach in addressing the financial crisis.